(3TQM HgLI GdfahS hfMdjgG eNJUQ GdHNGQis - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3Yf YHO Gddg Hf YeQ bGd eG QCjJ QShd Gddg Udi Gddg Ydjg hSde Udi UdGI dZjQ ejbGJgG EdG UdGJjf LeY Hjf GdeZQH hGdYTGA s
(3BNQgG (B:s
(3aNU GdEMSGf Edjg ef gPG GdSjO GdPi ef CLdg dMbg GdghGf HCLd GdeQGJH hgj GdeZaQI fLR GdLRA GdQGHY ef cJGH TQM HgLI GdfahS hfMdjgG eNJUQ GdHNGQi HMeO Gddg hYhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(97) s
Keywords: (3GdMOjK h GdeUWdMs